2011
DOI: 10.1186/1475-2840-10-69
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of neuregulin-1 in diabetic cardiomyopathy rats

Abstract: BackgroundDiabetic cardiomyopathy (DCM) is a disorder of the heart muscle in people with diabetes, which is characterized by both systolic and diastolic dysfunction. The effective treatment strategy for DCM has not been developed.MethodsRats were divided into 3 groups with different treatment. The control group was only injected with citrate buffer (n = 8). The diabetes group and diabetes treated group were injected with streptozotocin to induce diabetes. After success of diabetes induction, the rats with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 32 publications
5
55
1
Order By: Relevance
“…These observations may be different from previous studies with rhNRG-1 in diabetic models (22,23). In this study, absence of increased myocardial fibrosis was confirmed by three immunohistological staining methods and by mRNA analysis of fibrotic markers.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These observations may be different from previous studies with rhNRG-1 in diabetic models (22,23). In this study, absence of increased myocardial fibrosis was confirmed by three immunohistological staining methods and by mRNA analysis of fibrotic markers.…”
Section: Discussioncontrasting
confidence: 99%
“…In a chronic stabilized condition, NRG-1 may induce cardiomyocyte mitosis and promote myocardial regeneration (3). Also, protection against diabetic cardiomyopathy in type 1 diabetes has been described (22,23). Consistent with previous data, rhNRG-1 reversed cardiac MHC␣ downregulation and enhanced LV eNOS phosphorylation, presumably contributing to improved contractile function and reduced LV remodeling (22,24).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The ErbB4 agonist neuregulin1 (NRG1) rescues adult ventricular myocytes from hypoxia-reoxygenation-induced apoptosis, whereas the endothelium-selective deletion of NRG1 decreases the ability of the myocytes to tolerate an ischemic insult (Hedhli et al, 2011). Exogenous NRG1 also decreased the number of apoptotic cells and improved heart function in a rat model of diabetic cardiomyopathy with systolic and diastolic dysfunction (Li et al, 2011), and in cultured myocytes NRG1 inhibits the apoptosis induced by serum starvation (Zhao et al, 1998). Taken together, these studies indicate that NRG-ErbB4 signalling is important in cardiac protection.…”
Section: Introductionmentioning
confidence: 99%